KARYOTYPC STUDY IN 16O CLIN CALLY DIAGNOSED CASES OF MULTIPLE CONGEN ITAL ANOMALIES - BALWAN, WAHIED KHAWAR; GUPTA, SUBASH (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2011)
Karyotypic study carried out in a total of 160 clinically diagnosed cases of multiple congenital anomalies showed 60 individuals to (37.5%) have abnormal karyotypes. Of these 60 individuals (58; 36.25%) had Trisomy 21, 2, 1.25%) had Trisomy 13. All these 60 individuals showed phenotypic-cytogenetic heterogeneity. Present study supports the importance of chromosomal analysis in the investigation of individuals with genetic disorders of unknown origin so as to confirm the clinical diagnosis that is finally useful in genetic counselling.